Pengaruh Brand Image Dalam Mempengaruhi Word-Of-Mouth Konsumen Toko Daring Pakaian Muslim - Anita; Ghina Ardhillah; Khosyatillah Musfikhuna; Nadia Rizkiana; Usep Suhud (Fakultas Ekonomi Universitas Negeri Jakarta, 2020)
This research aims to test the factors that affect the word-of-mouth on daring consumer moslem clothing. In this case, there are five variables used to measure, namely word-of-mouth, trust, customer satisfaction, brand image and service quality. Data collection is conducted in Jakarta during the PSBB (large scale social restriction) period in April-May 2020. Data is collected using online questionnaires and respondents are selected using the purposive sampling technique. The total respondents in this study were 250 consisting of 54 men and 196 women. Data is processed using exploratory factor analysis and structural equation model. As a result, brand image has a positive and significant effect on customer satisfaction, brand image affects positively and significantly against the trust while the satisfaction variable has no significant effect on the trust, the brand image has no significant effect on service quality, trust has no significant effect on service quality, customer satisfaction has no significant effect on word-of-mouth, trust has no significant effect on word-of-mouth, service quality has no significant effect on word-of-mouth, and brand image has no significant effect on word-of-mouth.